Estrogen Regulates Protein Synthesis and Actin Polymerization in Hippocampal Neurons through Different Molecular Mechanisms - Briz, Victor; Baudry, Michel (Frontiers in Endocrinology, 2014)
Estrogen rapidly modulates hippocampal synaptic plasticity by activating selective membrane-associated receptors. Reorganization of the actin cytoskeleton and stimulation of mammalian target of rapamycin (mTOR)-mediated protein synthesis are two major events required for the consolidation of hippocampal long-term potentiation (LTP) and memory. Estradiol regulates synaptic plasticity by interacting with both processes, but the underlying molecular mechanisms are not yet fully understood. Here, we used acute rat hippocampal slices to analyze the mechanisms underlying rapid changes in mTOR activity and actin polymerization elicited by estradiol. Estradiol-induced mTOR phosphorylation was preceded by rapid and transient activation of both extracellular signal-regulated kinase (ERK) and protein kinase B (Akt) and by phosphatase and tensin homolog (PTEN) degradation. These effects were prevented by calpain and ERK inhibitors. Estradiol-induced mTOR stimulation did not require activation of classical estrogen receptors (ER), as specific ERα and ERβ agonists (PPT and DPN, respectively) failed to mimic this effect, and ER antagonists could not block it. Estradiol rapidly activated both RhoA and p21-activated kinase (PAK). Furthermore, a specific inhibitor of RhoA kinase (ROCK), H1152, and a potent and specific PAK inhibitor, PF-3758309, blocked estradiol-induced cofilin phosphorylation and actin polymerization. ER antagonists also blocked these effects of estrogen. Consistently, both PPT and DPN stimulated PAK and cofilin phosphorylation, as well as actin polymerization. Finally, the effects of estradiol on actin polymerization were insensitive to protein synthesis inhibitors, but its stimulation of mTOR activity was impaired by latrunculin A, a drug that disrupts actin filaments. Taken together, our results indicate that estradiol regulates local protein synthesis and cytoskeletal reorganization via different molecular mechanisms and signaling pathways.